Profile of 17ß-estradiol, vitellogenin, and egg diameter during gonad maturation process of striped catfish Pangasianodon hypophthalmus - Wahyu Pamungkas; Dedi Jusadi; Muhammad Zairin Junior; Mia Setiawati; Eddy Supriyono; Imron Imron (Jurnal Akuakultur Indonesia)
ABSTRACT